Muße und Gesellschaft - Dobler, Gregor; Riedl, Peter Philipp; Dobler, Gregor; Riedl, Peter Philipp (Mohr Siebeck)
Leisure (otium) is an unfettered lingering in time set loose from instrumental rationality and utilitarianism. It aims to be free from regimes of time and pressures to perform, that is, it aims at freedom set in time yet not subjected to time's dominion. Leisure may hence at first glance appear to be an individual experience and remove individuals from societal constraints, but it is also an eminently social phenomenon. Capacities for successfully claiming spaces of leisure for oneself are distributed in an extremely unequal manner. Freedom for leisure often becomes a defining and fiercely contested feature of specific social roles. This volume, which contains seventeen essays from ten different disciplines, illuminates leisure's societal dimension in varying historical and cultural contexts, while illustrating its symbolic capital in its respective manifestations.
German
Keywords: Cultural studies; Sociology; Leisure